Legal Policy in Village-Owned Enterprises After the Enactment of the Law on The Job Creation In The Framework of Village Society Welfare - Muin, Fatkhul (Jurnal Cita Hukum, 2021)
The essence of law is to provide welfare to society. Law as a tool of social engineering for society makes people obey it. Dynamic legal developments encourage progress towards society from various aspects of people's lives. One of them, the enactment of Law No. 11 of 2020 on Job Creation, encourages changes to the order of setting norms that affect other laws that are affected by it. One of those affected by the Job Creation Act is the establishment of BUMDes (Village-Owned Enterprises). Through the provisions of Article 117 and Article 185 b of Law Number 11 of 2020 concerning Job Creation, the government needs to establish a derivative norm that regulates Village-Owned Enterprises. In this provision, it is stated that Village Owned Enterprises, hereinafter referred to as BUMDes, are legal entities established by the village and/or together with villages to manage businesses, utilize assets, develop investment and productivity, provide services, and/or provide other types of business for the maximum welfare of the Village community. In a nutshell, the existence of Village-Owned Enterprises aims to prosper the village community, with the type of business sector owned and support the productivity of rural communities based on village community empowerment. In this study, a legal approach was used with the aim of exploring legal policies towards BUMDes with the enactment of the Job Creation Act.Keywords: Job Creation Act; BUMDes; welfareKebijakan Hukum Pada Badan Usaha Milik Desa Setelah Berlakunya Undang-Undang tentang Penciptaan Lapangan Kerja Dalam Rangka Kesejahteraan Masyarakat DesaAbstrakAdanya hukum sebagai alat rekayasa sosial bagi masyarakat. Karenanya, eksistensi hukum menjadikan masyakat taat terhadap hukum. Perkembangan hukum yang bersifat dinamis, mendorong kemajuan terhadap masyarakat dari berbagai aspek kehidupan masyarakat, salah satunya dengan disahkannya Undang-Undanag Nomor 11 Tahun 2020 tentang Cipta Kerja mendorong perubahan terhadap tatanan pengaturan norma-norma yang memberikan pengaruh terhadap undang-undang lain yang terdampak dengan Undang-Undang cipta kerja tersebut. Salah satu yang terdampak dengan adanya Undang-Undang Cipta Kerja adalah tentang pembentukan BUMDes (Badan Usaha Milik Desa). Melalui ketentuan  Ketentuan Pasal 117 dan Pasal 185 huruf b Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja, maka pemerintah perlu membentuk norma turunannya yang mengatur tentang Badan Usaha Milik Desa. Dalam ketentuan peraturan tersebut bahwa Badan Usaha Milik Desa yang selanjutnya disebut BUMDes adalah badan hukum yang didirikan oleh desa dan/atau bersama desa-desa guna mengelola usaha, memanfaatkan aset, mengembangkan investasi dan produktifitas, menyediakan jasa pelayanan, dan/atau menyediakan jenis usaha lainnya untuk sebesar-besarnya kesejahteraan masyarakat Desa. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan peraturan perundang-undangan dan literatur, dengan tujuan mengeksplorasi kebijakan hukum terhadap BUMDes dengan disahkannya Undang-Undang Cipta kerja. Hasil penelitian menyatakan bahwa keberadaan Badan Usaha Milik Desa bertujuan untuk mensejahterakan masyarakat desa, dengan jenis bidang usaha yang dimiliki dan menunjang produktivitas masyarakat desa dengan didasarkan kepada pemberdayaan masyarakat desa.Kata Kunci: UU Cipta Kerja; BUMDes; Kesejahteraan Правовая политика в отношении сельских предприятий после принятия Закона о создании рабочих мест для благосостояния сельских общинАннотацияСуществование права является инструментом социальной инженерии для общества. Следовательно, существование закона заставляет людей подчиняться закону. Динамичное правовое развитие, способствующее прогрессу в направлении общества из различных аспектов жизни людей, одним из которых является ратификация Закона № 11 от 2020 года о создании рабочих мест, поощряющего изменения в порядок регулирования норм, которые влияют на другие законы, на которые распространяется закон о создании рабочих мест. Одним из факторов, затронутых законом о создании рабочих мест, является создание BUMDes (сельских предприятий). В соответствии с положениями статьи 117 и статьи 185 буква b Закона № 11 от 2020 года о создании рабочих мест правительству необходимо установить производную норму, регулирующую деятельность сельских предприятий. В положениях постановления сельские предприятия, далее именуемые BUMDes, являются юридическими лицами, учрежденными деревнями и/или вместе с деревнями для управления предприятиями, использования активов, развития инвестиций и повышения производительности, предоставления услуг и / или предоставления других виды бизнеса для наибольшего благополучия деревенской общины. В этом исследовании используется качественный метод исследования с законодательным и литературным подходом с целью изучения правовой политики в отношении BUMDes с принятием Закона о создании рабочих мест. Результаты исследования показали, что существование сельских предприятий направлено на процветание деревенской общины с помощью частного сектора бизнеса и поддержки производительности сельских общин на основе расширения прав и возможностей деревенских общин.Ключевые слова: Закон о создании рабочих мест; BUMDes (сельские предприятия); социальное обеспечение.